-16-6-2g=-4(-g-20)

Simple and best practice solution for -16-6-2g=-4(-g-20) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -16-6-2g=-4(-g-20) equation:


Simplifying
-16 + -6 + -2g = -4(-1g + -20)

Combine like terms: -16 + -6 = -22
-22 + -2g = -4(-1g + -20)

Reorder the terms:
-22 + -2g = -4(-20 + -1g)
-22 + -2g = (-20 * -4 + -1g * -4)
-22 + -2g = (80 + 4g)

Solving
-22 + -2g = 80 + 4g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-4g' to each side of the equation.
-22 + -2g + -4g = 80 + 4g + -4g

Combine like terms: -2g + -4g = -6g
-22 + -6g = 80 + 4g + -4g

Combine like terms: 4g + -4g = 0
-22 + -6g = 80 + 0
-22 + -6g = 80

Add '22' to each side of the equation.
-22 + 22 + -6g = 80 + 22

Combine like terms: -22 + 22 = 0
0 + -6g = 80 + 22
-6g = 80 + 22

Combine like terms: 80 + 22 = 102
-6g = 102

Divide each side by '-6'.
g = -17

Simplifying
g = -17

See similar equations:

| y+3y-1=y | | -3g+4=9-8g | | 7x-x-10=-4 | | F(-4)=3x^2+5 | | 459.90=210x+119x | | 3=9+4c | | 14v+(-4v)= | | 5-2+8v=-9-4v | | y-7/16=-5/8 | | (-8x^6)^-4/3 | | 5-7w=-8w | | 459.90=210+119x | | x^2*x-20=0 | | 1-4j=-2j-7 | | (-8x^6)^-3/4 | | 4(7h+16)=-9h-2(-18h-13) | | -3d=-8d-10 | | -15x+7y+15x-13y= | | 5s+2=6s-6 | | -17g-(-4)=-30 | | C=38.89+0.25x | | -19-(-19)-18= | | 5-4(3w-3)=-6 | | 8=3u+4u | | 8=60+4x | | -7+3f=4f+3 | | y/3-2=5/6 | | 0=x^3(4-x) | | 7w-3=6w-5 | | 7s+-5=9 | | 81=9x+x^2 | | 8.0a-6=-0.6a+22 |

Equations solver categories